POLA EDUKASI DALAM SISTEM KEPERCAYAAN DI KALANGAN WANITA HAMIL MASYARAKAT MELAYU KUANTAN SINGINGI RIAU - Rr Sri Kartikowati (Marwah: Jurnal Perempuan, Agama dan Jender, 2015)
Within the Melayu Community, myths or strong traditional belief about pregnant woman is still practiced despite questionable. This study aims: (1) to seek the appreciation of pregnant women in the myths; (2) to interpret the educational value of myths; and (3) to design the educational pattern for pregnant woman's health. This study conducted in the village of Kotobaru, Regency of Kuantan Singingi. The data is gathered mainly from pregnant women (including women with toddler). Observation, documentation, and in-depth interview techniques are used to collect data; while the design of educational patterns is gathered through the focus group discussions. Its process involves professionals in health, education, and community development. The data is then analyzed with interactive analysis techniques. The study found some forms of myths that is still practiced among Melayu community. In addition we found that all the traditional belief or myths can be interpreted broadly to include psychological aspects, health, socio-cultural, and education. Patterns of health education of pregnant women is constructed in the basis of the Community Based Education (CBE) approach, supported by health and religious institutions.